Development of a hospital‐based program focused on improving healthcare value. Issue 10 (1st July 2014) - Moriates, Christopher; Mourad, Michelle; Novelero, Maria; Wachter, Robert M.
<x xml:space="preserve">Abstract</x> BACKGROUND Frontline physicians face increasing pressure to improve the quality of care they deliver while simultaneously decreasing healthcare costs. Although hospitals and physicians are beginning to implement initiatives targeting this new goal of healthcare value, few of them have a well‐developed infrastructure to support this work. METHODS In March 2012, we launched a high‐value care (HVC) program within the Division of Hospital Medicine at the University of California, San Francisco. The HVC program is co‐led by a physician and the division's administrator, and includes other hospitalists, resident physicians, pharmacists, and administrators. The program aims to (1) use financial and clinical data to identify areas with clear evidence of waste in the hospital, (2) promote evidence‐based interventions that improve both quality of care and value, and (3) pair interventions with evidence‐based cost awareness education to drive culture change. RESULTS We identified 6 ongoing projects during our first year. Preliminary data for our inaugural projects are encouraging. One initiative, which targeted decreasing nebulizer use on a high‐acuity medical floor (often using metered‐dose inhalers instead) led to a decrease in rates of more than 50%. CONCLUSIONS The HVC program is proving to be a successful mechanism to promote improved healthcare value and clinician engagement. Journal of Hospital Medicine 2014;9:671–677. © 2014 Society of Hospital Medicine